Binding interaction of 5-amino-2-mercaptobenzimidazole with Au-TiO2: inhibition of switch-on fluorescence. Issue 6 (3rd June 2022) - K. I., Dhanalekshmi; K., Jayamoorthy; Subash, B.; Magesan, P.; Ujam, Oguejiofo T.; Zhang, Xiang; Kadambary, K.
Abstract: Gold loaded TiO2 nanoparticles was synthesized and characterized by powder XRD, HR-TEM, and EDX analysis. The binding interaction of 5-amino-2-mercaptobenzimidazole (fluorochrome) with TiO2 and gold loaded TiO2 nanoparticles was discussed herein. The interaction of fluorochrome with TiO2 and Au-TiO2 nanoparticles has been studied by UV-visible, fluorescence, and FT-IR spectral techniques. Fluorescence emission occurs at 421 nm and this has been selectively enhanced by TiO2 nano semiconductor. This technique is sensitive to detect and estimate TiO2 nano semiconductor at a micromolar level. This switch-on fluorescence is obtained when fluorochrome is binds with TiO2 nanoparticles. This increase in fluorescence is suppressed when TiO2 nanoparticles is loaded with gold. This is because of chemo sensing nature of the gold. The strong adsorption of fluorochrome over the surface of nano semiconductor results in the electron transfer between fluorochrome and semiconductor. Further, the binding site of semiconductor with fluorochrome has been studied theoretically by molecular electrostatic potential diagram.